Characterizetion of Bioactive Compound of Sembung (Blumea balsamifera (L) Dc) Leaf Extract from Different Solvents - Mantra, Ida Bagus Ketut; Putra, I Nengah Kencana; Wrasiati, Luh Putu (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2020)
Sembung (Blumea balsamifera (L) DC) is a species plant on Blumea genus, andAstereceae (compositae) family. The leaf of Sembung is used by human as empiric treatment with extraction or infuse technique to become “jamu” , its has function as functional drink, because its consist of flavonoid and alkaloid compound, that has an antioxidant potency. The purpose of this research are to study of effect growth leaf level and some of organic solvent to characterizetion simplisia powder extract Sembung leaf. The methode of extraction by maseration, then analyze is done such as flavonoid, phenolic total, antioxidant capacity, vitamin C, IC50, and determine volatil compound on the best treatment by GC-MS. The result showed that very singnificant effect to all parameters analysis, and ethyl acetate extract on the tip of Sembung leaf is the best treatment, that consist of flavonoid (204,58 mg QE/g db), phenolic total (225,33 mg GAE/ g db), vitamin C (451,92 mg/g db), antioxidant capacity (501,97 mg GAEAC/g db), and IC 50%(37,09 ppm). The GC-MS analysis showed there are benzena compound, monoterpene (camphor, L-berneol), sesquiterpene (?-guaiene, caryophyllene, humulene) and diterpene (neophytadiene) on the best treatment.